2014
DOI: 10.1007/s13224-014-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Level on Day 2 and Day of Trigger: A Potential Predictor of the IVF-ET Success

Abstract: Objective To evaluate role of serum estradiol levels in predicting likelihood of pregnancy in women undergoing GnRH-a protocol in IVF-ET cycles. Design A 3-year retrospective analysis of estradiol levels on down-regulated day 2, day 6, and day of hCG trigger and subsequent clinical pregnancy rates. Setting A university hospital tertiary referral centre. Population or Sample Women undergoing IVF treatment. Methods Hormonal assessment on the down-regulated day 2, day 6, and day of hCG trigger. Main Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…36 The optimal level of estradiol on the day of hCG triggering is more likely to be associated with a good number of oocytes and possibly better quality embryos than with inferior levels of estradiol. Hence, these data provided The prognostic value of serum estradiol level at the time of hCG triggering in fresh IVF/ICSI cycles has been previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 The optimal level of estradiol on the day of hCG triggering is more likely to be associated with a good number of oocytes and possibly better quality embryos than with inferior levels of estradiol. Hence, these data provided The prognostic value of serum estradiol level at the time of hCG triggering in fresh IVF/ICSI cycles has been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic value of serum estradiol level at the time of hCG triggering in fresh IVF/ICSI cycles has been previously reported. 36 The optimal level of estradiol on the day of hCG triggering is more likely to be associated with a good number of oocytes and possibly better quality embryos than with inferior levels of estradiol. Elevated or diminished levels of estradiol could impair the maturation of the oocyte cytoplasm and decrease the probability of achieving a pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies had different results even using the same method. Data showed that higher E 2 levels would probably lead to a higher pregnancy rate [5,19,20,29],or, that there was no association between E 2 levels on the day of hCG administration and clinical pregnancy [8,10,17,18,23,30,31]. However, an analysis of 400,135 IVF cycles showed that the live birth rate (LBR) rose with an increase in the number of eggs, up to 15, then plateaued between 15 and 20 eggs and steadily declined beyond 20 eggs.…”
Section: Discussionmentioning
confidence: 99%
“…On day 1 of the cycle, serum estradiol (E2) was measured and a transvaginal ultrasonography was performed. If E2 was less than 50 pg/mL [13], stimulation was started on day 2 of the cycle with a follicle-stimulating hormone and luteinizing hormone preparation administered intramuscularly with halving the dose of triptorelin. Follow-up was conducted every two to three days at the start of induction and every one to two days thereafter until the end of induction.…”
Section: Methodsmentioning
confidence: 99%